2017
DOI: 10.1007/s10943-017-0393-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian version of the Daily Spiritual Experiences Scale (DSES) in Pregnant Women: A Proper Tool to Assess Spirituality Related to Mental Health

Abstract: Assessing spirituality in healthy pregnant women may lead to supportive interventions that will improve their care. A psychometrically valid measure such as the Daily Spiritual Experiences Scale (DSES) may be helpful in this regard. The current study sought to adapt a Persian version of DSES for use in pregnancy. A total of 377 pregnant women were recruited from three general hospitals located in Tehran, Iran. Administered scales were the DSES, Duke University Religion Index, Santa Faith scale, and Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The reliability of the DSES in both groups was confirmed by the high Cronbach's alpha value (0.917, respectively 0.964). The result of our study is comparable to those reported in other studies, in which the alpha coefficient was above 0.90 (Kalkstein & Tower, 2009;Ellison & Fan, 2008;Ng et al, 2009;Mayoral et al, 2010;McCauley et al, 2008;Saffari et al, 2017;Soósová & Mauer, 2021). Cronbach's alpha did not increase if particular items were removed from the scale, except for items 13 ("I feel a selfless caring for others.")…”
Section: Discussionsupporting
confidence: 91%
“…The reliability of the DSES in both groups was confirmed by the high Cronbach's alpha value (0.917, respectively 0.964). The result of our study is comparable to those reported in other studies, in which the alpha coefficient was above 0.90 (Kalkstein & Tower, 2009;Ellison & Fan, 2008;Ng et al, 2009;Mayoral et al, 2010;McCauley et al, 2008;Saffari et al, 2017;Soósová & Mauer, 2021). Cronbach's alpha did not increase if particular items were removed from the scale, except for items 13 ("I feel a selfless caring for others.")…”
Section: Discussionsupporting
confidence: 91%
“…Findings of the Exploratory Factor Analysis (EFA) revealed a single factor that explained 59% of the total scale variance. [ 28 ] In the present study, the reliability of the questionnaire was evaluated through internal consistency, and Cronbach’s alpha for the entire questionnaire was reported to be 0.89, suggesting its good reliability.…”
Section: Methodsmentioning
confidence: 71%
“…There are five questionnaires that evaluate spirituality and have been frequently administered in spirituality health studies. Daily Spiritual Experience Scale ( 30 ), Parsian and Dunning's Spirituality Questionnaire ( 31 ), Spiritual Assessment Inventory (SAI) ( 32 ), Spirituality Perspective Scale ( 33 ), and Spiritual Attitude and Ability Questionnaire ( 34 ). They generally evaluate spiritual beliefs, behaviors, awareness and ability.…”
Section: Resultsmentioning
confidence: 99%